2021
DOI: 10.3889/oamjms.2021.7229
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Stromal Vascular Fraction Administration in Stimulating Graft Healing Process after Anterior Cruciate Ligament Reconstruction Surgery in Rattus norvegicus

Abstract: Introduction: Ligament injuries commonly occur in the knee region, and the anterior cruciate ligament (ACL) being the most usually injured. Currently, autograft or allograft is the most common material used for ACL reconstruction surgery. The result of the ACL reconstruction depends on the healing process of the graft or ligamentization between graft and bone tunnel. This study aims to evaluate the effect of Stromal Vascular Fraction (SVF) intratunnel injection to stimulates graft healing following ACL reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…However, regarding the condition of the ACLR, there has been only one animal study. Using a rat model, Santoso et al [ 29 ] reported that SVF stimulated graft healing after ACLR, as evidenced by histological assessments. To the best of our knowledge, this work is the first clinical study to investigate the biologic augmentation of ACLR with SVF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, regarding the condition of the ACLR, there has been only one animal study. Using a rat model, Santoso et al [ 29 ] reported that SVF stimulated graft healing after ACLR, as evidenced by histological assessments. To the best of our knowledge, this work is the first clinical study to investigate the biologic augmentation of ACLR with SVF.…”
Section: Discussionmentioning
confidence: 99%
“…In orthopedic medicine [ 19 ], SVF has been used in treating patients with certain conditions, mainly degenerative cartilage diseases [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. However, to date, there has been only one animal study reporting that SVF stimulated graft healing after ACLR [ 29 ]. Thus, clinical evidence is timely required in defining whether SVF has biologically augmented effects on ACLR.…”
Section: Introductionmentioning
confidence: 99%